Pengaruh Media Audio Visual dan Media Visual untuk Meningkatkan Hasil Belajar Three Point Bola Basket di SMA N 8 Semarang - Muhammad Shiddiq At Tamimi; Bertika Kusuma Prastiwi; Muh Isna Nurdin Wibisana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The use of audio-visual and visual media is necessary to improve learning outcomes. This study aims to determine the effect of audio-visual and visual media on the learning outcomes of three point basketball shooting among students at SMA Negeri 8 Semarang, and to compare the effectiveness of the two learning media. This study used a quantitative approach with a quasi-experimental method through a two-group pretest-posttest design. The research sample consisted of 72 tenth-grade students divided into two groups, namely class X 5 as the experimental class using audio-visual media and class X 3 as the control class using visual media, with each group consisting of 36 students. The data analysis techniques used were the normality test, homogeneity test, and t-test (Independent Sample t-test) with the assistance of SPSS Indonesia. The results showed that: (1) there was no significant difference in initial ability between the two groups based on the pretest scores (Sig. = 0.085 > 0.05); (2) the results of the Independent Sample t-test on the posttest showed a significance value of 0.004 (p < 0.05); (3) the average posttest score of the experimental class was 89.06, higher than the control class at 86.64; and (4) audio-visual media was more effective than visual media in improving learning outcomes for the three point basketball material. Thus, it can be concluded that audio-visual media is more effective than visual media in improving the learning outcomes of three point basketball shooting among students at SMA Negeri 8 Semarang. Keywords: Basketball, Learning Outcomes, Audio Visual Media, Visual Media, Physical Education and Health (PJOK), Three Point